Sex Differences in Pediatric Sepsis Mortality: A Systematic Review and Meta-Analysis - Uchenna K. Kennedy, MD; Juliette Moulin; Lea Bührer, MSc; Joanne Lim Fang Nian; Leyla Halter; Luzius Böhni; Melisa Güzelgün; Kusum Menon, MD, MSc; Jan Hau Lee, MBBS, MCI; Luregn J. Schlapbach, MD, PhD, FCICM; Ulrike Held, PhD (Critical Care Explorations)
OBJECTIVES:. Pediatric sepsis remains a leading cause of childhood mortality worldwide. Sex differences have been shown to modify risk factors, treatment, and outcome of various diseases, and adult studies revealed sex differences in pathophysiological responses to septic shock. We aimed to perform a systematic review and meta-analysis on the association of sex with outcomes in hospitalized children with sepsis. DATA SOURCES:. Medline and Embase databases were searched for studies of children < 18 years with sepsis published between January 01, 2005, and March 31, 2022. STUDY SELECTION:. We included cohort studies, and randomized controlled trials in children greater than or equal to 37-week-old postconception to 18 years which included sepsis, severe sepsis or septic shock, and mortality as an outcome. DATA EXTRACTION:. Study characteristics, patient demographics, and illness severity scores were extracted from eligible articles. Random-effects meta-analysis was performed. DATA SYNTHESIS:. We screened 14,791 studies, with 912 full-text reviews and inclusion of 124 studies. The total population involved 426,163 patients, of which 47% (201,438) were girls. Meta-regression showed moderate evidence for a higher mortality in boys compared with girls. The estimated risk difference of mortality between boys and girls with all types of sepsis was −0.005 (95% CI, −0.0099 to −0.00001; p = 0.049), indicating slightly higher mortality for boys. When including the World Bank income level as a moderator, the effect was −0.008 (95% CI, −0.013 to −0.002; p = 0.005). CONCLUSIONS:. This large systematic review and meta-analysis on sex differences in pediatric sepsis mortality showed moderate evidence for a higher sepsis mortality in boys compared with girls. The effect persisted when adjusting for country’s income level.